FIELD EVALUATION OF WATER APPLICATION UNIFORMITY IN TRICKLE IRRIGATION SYSTEM - Reddy, K.S.; Rajput, T.B.S. (Journal of Soil and Water Conservation, 2022)
A trickle irrigation system was laid out in afield experiment to monitor discharge rate of emitters and hydraulic heads along laterals at different operating pressures (0.5 to 1.7 kg/cm2). the system parameters including co-efficients of manufacturing and hydraulic variations were detemined based on the observed discharge rates of emitters and pressure heads respectively. The uniformity indices of water application were estimated at selected operating pressures adopting eight different methods suggested by different research workers. The Christiansen equation resulted in the highest values of uniformity co-efficients in comparison to all other methods. The method suggested by Beriami and Hore (1946) was found to result in reliable estimates in case of undulating topography. Six methods resulted in maximum uniformity co-efficients of water application 1.0 kg/cm2 suggesting it to be optimal operating pressure for the trickle system.